2016
DOI: 10.1080/03630242.2016.1243608
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives from health-care providers and women about completing human papillomavirus (HPV) self-testing at home

Abstract: Cervical cancer (CC) incidence and mortality rates are increased, and CC screening rates are low among Appalachian Ohio women. Mailing human papillomavirus (HPV) self-tests to women to complete at home is a potential new strategy to engage women in CC screening. The authors aimed to gain insights into the perceived acceptability of mailed HPV self-tests. Focus groups were conducted (August 2014–January 2015) among providers (physicians, nurse practitioners, nurses) and women in Appalachian Ohio. Providers (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(74 citation statements)
references
References 27 publications
(39 reference statements)
1
65
0
8
Order By: Relevance
“…In this and two similar studies conducted in Ohio and Southwest Virginia, healthcare providers expressed concern about the efficacy of self-collection for HPV testing because they were uncertain about women’s ability to understand the self-collection instructions and collect adequate samples. 18,19 As research on self-collection advances, there is a need to communicate key findings with healthcare providers; there is limited research on interventions to educate healthcare providers about self-collection for HPV testing. 20 Healthcare providers in Ohio were also wary of self-collection because HPV testing alone is not currently recommended as a screening strategy by some key organizations in the United States, although the U.S. Food and Drug Administration (FDA) approved the cobas HPV test for use in primary cervical cancer screening in women aged 25 years or older.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this and two similar studies conducted in Ohio and Southwest Virginia, healthcare providers expressed concern about the efficacy of self-collection for HPV testing because they were uncertain about women’s ability to understand the self-collection instructions and collect adequate samples. 18,19 As research on self-collection advances, there is a need to communicate key findings with healthcare providers; there is limited research on interventions to educate healthcare providers about self-collection for HPV testing. 20 Healthcare providers in Ohio were also wary of self-collection because HPV testing alone is not currently recommended as a screening strategy by some key organizations in the United States, although the U.S. Food and Drug Administration (FDA) approved the cobas HPV test for use in primary cervical cancer screening in women aged 25 years or older.…”
mentioning
confidence: 99%
“…19 Currently, self-collection for HPV testing is mostly being examined as a strategy to reach women who do not attend or have access to regular screening at health centers; the effect of HPV self-collection on possibly reducing women’s clinic visit attendance or interactions with healthcare providers needs to be examined as implementation research progresses and HPV self-collection strategies and target populations are better defined.…”
mentioning
confidence: 99%
“…In Figure 1 we present the study selection diagram. In total, we retained 32 studies, four used qualitative (23)(24)(25)(26) and 28 used quantitative methodology (2,(16)(17)(18)(19)(20) . Included studies covered HCPs opinions from five continents: Europe (i.e., UK (47) , Germany (38) and Italy (39) ), North America (i.e., Canada (24,26,35) and the US (2, 16-20, 23, 29-31, 34, 36, 40-44, 46) ), Africa (i.e., Cameroon (28) and Nigeria (25) ), Asia (i.e., China (27) , Jordan (45) ,South Korea (33) and Thailand (37) ) and Oceania (i.e., Australia (32) ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite a slightly lower sensitivity and specificity in detecting cervical intraepithelial neoplasia (CIN2 and CIN3) of HPV testing on self-samples than of HPV testing on a clinician-taken sample (54,55) , Nelson et al (2017) found that 97% of women found selfsampling to be generally acceptable, 65% would prefer self-sampling over clinician-based sampling for HPV testing and considered self-sampling less embarrassing, respecting privacy and easy to use (56) . In our review, we found that HCPs viewed self-sampling as a facilitator of HPV testing as it alleviates women's concerns about privacy and body discomfort during Pap examination, has the potential to reach women in underserved locations and reduces the burden of women's return to the medical system (23,24) . Strategies to increase HCPs recommendations for self-sampling should take into consideration HCPs worries that self-sampling could be associated with missed opportunities to address other health issues and that women's decreased health literacy represents a barrier to an efficient screening, mostly due to poor quality of the self-collected sample (23,31) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation